CLOUD COMPUTING ADOPTION STRATEGIES AT PT TASPEN INDONESIA, Tbk - Julirzal Sarmedy; Bachtiar H. Simamora (CommIT (Communication and Information Technology) Journal, 2014)
PT. Taspen as Indonesian institution, is responsible for managing social insuranceprograms of civil servants. With branch offices and business partners who are geographicallydispersed throughout Indonesia, information technology is very important to support thebusiness processes. Cloud computing is a model of information technology services that couldpotentially increase the effectiveness and efficiency of PT. Taspen information system. Thisstudy examines the phenomenon exists at PT. Taspen in order to adopt cloud computing inthe information system, by using the framework of Technology-Organization-Environment,Diffusion of Innovation theory, and Partial Least Square method. Organizational factor isthe most dominant for PT. Taspen to adopt cloud computing. Referring to these findings,then a SWOT analysis and TOWS matrix are performed, which in this study recommendsthe implementation of a strategy model of cloud computing services that are private andgradually in process.